Keutamaan Sujud dalam Shalat Studi Takhrij dan Syarah Hadis - Are Adriyanto; Susanti Vera; Reza Pahlevi Dalimunthe (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith regarding the virtues of prostration in prayer through the application of takhrij and syarah hadith studies. This research method uses a qualitative approach through literature study with contemporary analysis. The results of this study found that the hadith about the virtue of prostration in prayer is authentic in terms of sanad and matan. The discussion of this study states that the benefits of prostration in prayer are that Al-Qodhi said: the words bowing and prostration are used as a designation for prayer because the position of other prayer movements is the same as the usual movement, namely standing and sitting. The standing position is the first order to humble oneself to Allah Ta'ala, and the middle order is bowing and the peak is prostration. All of them show the peak of humility and self-servitude to Allah. This is in line with the purpose of establishing prayer, which is to humble oneself before Allah and glorify Him. The conclusion of this study is that the prostration movement in prayer has the meaning of submission, besides that the attitude of prostration is also good for physical and spiritual health and improves the quality of our worship to Allah.